Enhanced dye sequestration with natural polysaccharides-based hydrogels: A review - Majeed, Fiza; Razzaq, Ammarah; Rehmat, Shabnam; Azhar, Irfan; Mohyuddin, Abrar; Rizvi, Nayab Batool (Carbohydrate polymers, 2024)
Due to the expansion of industrial activities, the concentration of dyes in water has been increasing. The dire need to remove these pollutants from water has been heavily discussed. This study focuses on the reproducible and sustainable solution for wastewater treatment and dye annihilation challenges. Adsorption has been rated the most practical way of the several decolorization procedures due to its minimal initial investment, convenient utility, and high-performance caliber. Hydrogels, which are three-dimensional polymer networks, are notable because of their potential to regenerate, biodegrade, absorb bulky amounts of water, respond to stimuli, and have unique morphologies. Natural polysaccharide hydrogels are chosen over synthetic ones because they are robust, bioresorbable, non-toxic, and cheaply accessible. This study has covered six biopolymers, including chitosan, cellulose, pectin, sodium alginate, guar gum, and starch, consisting of their chemical architecture, origins, characteristics, and uses. The next part describes these polysaccharide-based hydrogels, including their manufacturing techniques, chemical alterations, and adsorption effectiveness. It is deeply evaluated how size and shape affect the adsorption rate, which has not been addressed in any prior research. To assist the readers in identifying areas for further research in this subject, limitations of these hydrogels and future views are provided in the conclusion. [Display omitted] •Different physiochemical interactions that result in the adsorption of pollutants.•Discussion and comparison of preparation strategies, chemical modifications, and adsorption outcomes.•The effect of modifiers and factors on the adsorption efficiency of hydrogels.•Critical study of the morphological aspects on hydrogel performance for dye removal.